Bioinspired interface design of multifunctional soy protein-based biomaterials with excellent mechanical strength and UV-blocking performance. (1st November 2021) - Li, Kuang; Jin, Shicun; Zhou, Ying; Luo, Jing; Li, Jiongjiong; Li, Xiaona; Shi, Sheldon Q.; Li, Jianzhang
Abstract: Renewable and biodegradable plant-derived biomaterials are considered an ideal alternative to non-biodegradable petrochemical plastics. However, the inherent cohesion and mechanical properties of biopolymers are usually insufficient to meet the requirements of practical applications. Inspired by the supramolecular chemistry of mussels, we report a facile and sustainable strategy for fabricating a high-performance soy protein (SP)-based film by incorporating polyvinylpyrrolidone (PVP)-functionalized lignosulfonate (LS) hybrids. In this process, the polymerized LS molecules form rigid skeletal domains, and the PVP chains serve as soft components to ensure the flexibility of the composites. An interconnected cross-linking network was constructed in the SP/PVP@LS film via multiple non-covalent interactions including hydrogen bonding, hydrophobic interactions, and π–π interactions. As a result of the synergistic effect of supramolecular interactions, the tensile strength and toughness of the resulting film were significantly enhanced to 16.15 MPa and 23.50 MJ/m 3, corresponding to increases of 111.39% and 386.54% relative to the pristine SP film. The SP/PVP@LS film also shows excellent ultraviolet-light resistance, improved flame retardancy, and favorable thermal stability owing to the unique aromatic ring structure and the ketones, phenol units, and chromophore functional groups in the PVP@LS hybrids. The bioinspired design strategy provides an innovative and facile route for producing multifunctional SP-based films for various prospective applications in fields such as biomass adhesives, active packaging, UV-protective coatings, and flame retardants. Graphical abstract: Image 1 Highlights: A supramolecular chemistry strategy is used to prepare a soy protein-based film. Lignosulfonate (LS) hybrids are functionalized by polyvinylpyrrolidone (PVP). Multiple cross-linking networks are constructed via noncovalent interactions. Tensile strength and toughness of the film were increased by 111.39% and 386.54%. The film shows enhanced UV-blocking, flame retardancy, and thermal stability.